Papillary Fibroelastoma of the Heart: Controversies in Histogenesis, Detection, and Surgical Strategy - Volodymyr V. Isaіenko; Rostyslav M. Vitovskyi; Dmytro М. Dyadyun; Oleksandr A. Pishchurin; Valentina P. Zaharova; Marina M. Serdyuk; Oleksandr A. Beregovyi (Ukrainian Journal of Cardiovascular Surgery, 2025)
Background. Papillary fibroelastoma (PFE) is a small endocardial tumor, typically located on heart valves, with a disproportionately high embolic risk. Despite classic echocardiographic descriptions, debate continues regarding its origin (reactive vs. “thrombo-endothelial,” potentially arising from Lambl’s excrescences), the indications for surgery in asymptomatic patients, and the role of minimally invasive or percutaneous resection.Aim. To analyse the prevalence and characteristics of PFE among cardiac tumors based on our institutional experience and current literature, to address controversial aspects, and to outline surgical strategies according to neoplasm localization.Materials and Methods. Between 1969 and 2025, 1046 patients with cardiac tumors underwent surgery at the Amosov National Institute of Cardiovascular Surgery (Kyiv, Ukraine). Myxomas accounted for 89.4 % of benign cardiac tumors, while PFE accounted for 1.3 % of all cases and 34.2 % of non-myxomatous benign tumors.Results Most PFEs were valvular, predominantly located in the aortic and mitral positions. Although frequently asymptomatic, they were associated with embolic events. Surgical “shave excision” with valve preservation enabled complete resection with minimal morbidity. In large series (Mayo Clinic and other centres), surgical outcomes are excellent; however, recent data show a significantly higher long-term recurrence rate for aortic PFEs than previously reported, reaching 15-16 % over 10 years, underscoring the need for prolonged echocardiographic follow-up [13]. Percutaneous ablation is emerging as an option for selected asymptomatic patients, though robust evidence remains limited.Conclusions. PFE is a small but clinically significant tumor with serious embolic potential. Optimal management includes timely recognition, valve-sparing surgical excision, and structured postoperative surveillance. Further studies are needed to clarify its histogenesis, establish operative thresholds for asymptomatic patients, and define the role of percutaneous interventions.